2023
DOI: 10.3390/cancers15020520
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate, Lipid, and Apolipoprotein Biomarkers in Blood and Risk of Thyroid Cancer: Findings from the AMORIS Cohort

Abstract: Background: Previous studies have examined the link between blood metabolic biomarkers and risk of thyroid cancer, with inconclusive results. We performed a cohort study based on the Swedish Apolipoprotein-Related Mortality Risk (AMORIS) Cohort, including 561,388 individuals undergoing health examinations during 1985–1996 with a follow-up of >30 years. Methods: Newly diagnosed cases of thyroid cancer were identified from the Swedish Cancer Register. We assessed the associations of nine blood biomarkers of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
4
2
Order By: Relevance
“…( 32 ). Some retrospective observational studies have reported an association between total cholesterol ( 31 ) and apolipoprotein A1 ( 33 ) with thyroid cancer, which is somewhat inconsistent with the results of our study. In the observational study, HDL may be a confounding factor for other lipid profiles.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…( 32 ). Some retrospective observational studies have reported an association between total cholesterol ( 31 ) and apolipoprotein A1 ( 33 ) with thyroid cancer, which is somewhat inconsistent with the results of our study. In the observational study, HDL may be a confounding factor for other lipid profiles.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, a Korean epidemiological study discovered that obese women with low HDL cholesterol levels were at a heightened risk of developing thyroid cancer ( 29 , 30 ). Similarly, the Swedish Apolipoprotein-Related Mortality Risk (AMORIS) Cohort study demonstrated that thyroid cancer risk was associated with blood levels of total cholesterol (TC) and HDL-C ( 31 ). HDL-C level was found to be a statistically significant independent predictor of thyroid cancer in a model developed by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies confirmed that reduced APOA1 levels were associated with a worse prognosis and aggressive thyroid tumor characteristics [176]. Nevertheless, the previous findings contradict with a recent study that found no association between APOA1, APOB, or APOB/APOA1 levels and the risk of thyroid cancer [177]. In fact, it was found that elevated HDL-C and cholesterol levels, which are regulated by APOA1, were associated with a reduced thyroid cancer risk [177].…”
Section: Apolipoproteins In Thyroid Cancermentioning
confidence: 78%
“…On the other hand, in some previous studies, the lower levels of TC in thyroid cancer cases might be partially attributed to a reverse causal relationship, where thyroid cancer patients showed a decrease in all lipid biomarker (including TC) levels studied in the decade before cancer diagnosis, while the control group showed a sustained increase in TC levels during the same period due to aging. A large-scale cohort study based on the Swedish AMORIS cohort with 30 years of follow-up found that a higher level of TC and HDL-C was negatively correlated with a lower risk of thyroid cancer ( 7 ). However, a recent meta-analysis of 42 studies showed that there was no relationship between TC risk and dyslipidemia ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that a disordered serum lipid profile may be related to the thyroid gland ( 6 , 7 ). There are generally seven serum lipid tests in medicine: triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B), and ratio of Apo B to Apo A1.…”
Section: Introductionmentioning
confidence: 99%